MEMBENTUK GENERASI YANG BERKARAKTER (TANTANGANNYA BAGI PENDIDIKAN DI INDONESIA) - Idham Kholid (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Once the importance of charaterized generation, character education, Pancasila values education and antiradicalism education are inevitable. On the other hand, the latest issue that can be considered the most potential to disrupt the unity of the Unitary Republic of Indonesia is the idea of radicalism. In order to ensure that today's generation and future will be able to maintain the integrity of the Unitary State of the Republic of Indonesia, it needs to be printed by generations that have strong character, have an appreciation of the values of Pancasila and also have antiradicalism attitude. Thus, it takes the process and the ideal vehicle to form the intended generation. In this context, the most likely process is education. Education in Indonesia should be oriented towards the development of cognitive, affective, and psychomotor aspects simultaneously.